A mixed methods analysis of the monitoring of oral anti-cancer therapies. (October 2021) - O'Mahony, Cian; Murphy, Kevin D.; Byrne, Stephen
Abstract: Purpose: Oral anti-cancer therapies offer advantages over parenteral therapies in terms of their non–invasive nature and reduced intrusiveness. However, the shift from directly observed administration of these therapies to home administration means that continuous monitoring is needed. The oral anti-cancer therapy market is rapidly growing, with an ever-increasing number of new medicines available for the patients presenting with cancer illnesses. This study aims to (i) evaluate both the cost of providing monitoring consultations of oral anti-cancer therapies, and (ii) to assess the experience of cancer therapy nurses responsible for the monitoring and their opinions of the quality of the service. Methods: This study provides a mixed methods evaluation of the monitoring of oral anti-cancer therapies. Nurses were asked to record the time taken for them to perform their monitoring duties, and staff related costs were calculated using publicly available salary data. Patient-related costs were calculated using the Human Capital method. Nurses were asked to discuss their experience of monitoring oral anti-cancer therapies in semi-structured interviews. These interviews were subsequently analysed using thematic analysis. Results: 201 recordings and their associated costs were documented. The median consultation time was 33 min, costing €22.10 using Clinical Nurse Specialist salary figures and €26.51 using Advanced Nurse Practitioner salary figures. The associated patient cost was €14.06. Themes of the effect of Covid-19 on the service, expanding and complicated care package requirements, the need for dedicated oral clinics and the future of the service emerged from the interview data. Conclusion: The monitoring service provided by nurses may be undervalued. The commitment to fully dedicated oral anti-cancer therapy clinics and an increase in staff to align with the ongoing increase in service demand is seen as vital for the continued safe and effective delivery of this specialist cancer service. Highlights: Oral anti-cancer therapies require regular monitoring consultations due to the increased risk of adverse drug reactions. A mixed methods evaluation of these monitorings was carried out. The service was shown to be at a near breaking point, particularly concerning given the imminent increase in patients. Dedicated oral anti-cancer clinics will allow for both improved capacity and quality of the service.